Axiological Perspectives on the Development of Sustainable Natural Food Preservatives Derived from Sea Grapes (Caulerpa spp.) - Moegiratul Amaro; M Sarjan; Siska Cicilia; Mutia Devi Ariyana; Ida Ayu Widhiantari; Hanifah Ayu; Sudarli; Gunawan; Amrullah; Husnul Jannah; Aida Muspi’ah (Journal of Food and Agricultural Product, 2026)
The use of synthetic preservatives in the food industry has raised significant health and environmental concerns due to their carcinogenic potential, endocrine-disrupting effects, allergenic risks, and toxic residues in ecosystems. This study examines the potential of sea grapes (Caulerpa spp.) as a natural food preservative from an axiological perspective, encompassing health values, environmental ethics, and socio-economic benefits. Caulerpa racemosa and Caulerpa lentillifera contain polyphenols, flavonoids, tannins, terpenoids, alkaloids, and sulfated polysaccharides (ulvan, fucoidan), which exhibit strong antioxidant and antimicrobial activities. These compounds have been shown to inhibit pathogenic bacteria, slow oxidation, and function effectively as preservatives in various forms such as extracts, edible films, powders, and functional food applications. From an axiological standpoint, the use of Caulerpa supports food safety, public health, environmental sustainability, and economic empowerment of coastal communities through product diversification and value-added processing of renewable marine bioresources. Despite its promising potential, challenges remain, including variability in metabolite content, the need for standardization, and long-term safety assessments. This study highlights Caulerpa spp. as a strategic candidate for developing safe, eco-friendly, and sustainable natural food preservatives. Keywords: Sea grapes, Antimicrobial activity, Antioxidants, Caulerpa spp., Natural preservatives